Public policies for women and domestic violence - Santos, T. F.; Nascimento, C. S.; Souza, K. O.; Silva, C. E. (Scientia Plena, 2012)
Violence against women is a universal problem that affects thousands of people from different groups, and not usually restricted to a social, economic, religious, or cultural group. It is known that domestic violence is a serious problem that affects families from different countries and that there is a concealment of the offense occurred. Knowing that the complaint is a highly personal act inherent to the victim, hence its omission hinders the performance of possible assistance to these women who are assaulted in their family context. In this context, this study aimed to describe the policies for women in Brazil comparing them with the actions that occur in the municipality of Paripiranga, and also to discuss the importance of the complaint against the aggressors. Bibliographic information through a detailed study on the subject in books and journals in this field of study was collected. Interviews were conducted with the delegate and the city promoter of Paripiranga (BA) to collect information about the subject, especially the numbers of procedures referred to court, handling complaints, as well as the results of these procedures. There were also interviews with a sample of battered women in the municipality to identify the reasons, reactions and results of the aggression. The data analyzed highlighted that from 2006 to 2010 there was a considerable increase in the police procedures related to violence against women, showing that in 2006 there were 5%, in 2007, 21%, in 2008, 28%, in 2009, 33%, and in the first semester in 2010, 13%. It is also concluded that most of the attackers are their own companions, ex-husbands/ex-boyfriends, followed by fathers, uncles, neighbors, sons in law / daughters in law and nephews. The data also show that most abused were female, with 97% of cases, with only 3% of assaults against men.